Assessment of equivalent substrate stiffness and mechanical properties of sustainable alkali-activated concrete containing recycled concrete aggregate. (June 2022) - Damrongwiriyanupap, Nattapong; Srikhamma, Todsaporn; Plongkrathok, Chittinat; Phoo-ngernkham, Tanakorn; Sae-Long, Worathep; Hanjitsuwan, Sakonwan; Sukontasukkul, Piti; Li, Long-yuan; Chindaprasirt, Prinya
Abstract: The effects of using recycled concrete aggregate (RCA) as coarse aggregate on the equivalent substrate stiffness and mechanical properties of sustainable alkali-activated concrete were investigated in this paper. High-calcium fly ash (HFA) and commercial silica fume (SF) were used as the precursors for producing the alkali-activated high-calcium fly ash concrete (AAHFAC). Sodium hydroxide (SH) and sodium silicate (SS) solutions were used as alkaline activator solutions with the constant SS/SH ratio of 1.0 and liquid-binder (L/B) ratio of 0.50. The natural coarse aggregate (NCA) used in this study was crushed limestone and replaced with RCA at the rates of 0%, 20%, 40%, 60%, 80%, and 100% by volume. The setting time, compressive strength, elastic modulus, Poisson's ratio, and bond strength obtained by pull-out tests of AAHFAC and Portland cement concrete (NC) were investigated. Experimental results showed that the use of RCA to replace NCA resulted in reducing the setting time of concrete. Also, the setting time of the AAHFAC with and without SF were shorter than that of NC mixes for all of RCA replacement level. The use of RCA had a positive effect on the mechanical properties of alkali-activated binder; however, they declined at NC mixes. Therefore, the use of RCA in alkali-activated binder concrete is an excellent alternative for sustainable concrete since it allows for the substitution of natural resource components while somehow producing low CO2 emissions.